ASSOCIATION BETWEEN VEGF +936 C>T GENE POLYMORPHISM WITH THE DEGREE OF ATROPHY IN GASTRITIS PATIENTS - Karina Dwi Swastika, GontarAlamsyah Siregar, Dharma Lindarto, Ilhamd (International Journal of Research Science and Management, 2020)
In the process of gastritis become its deadly sequel, gastric cancer, some genetic factors are thought to play a role. VEGF is a neoangionesis factor that involved in this process. Some polymorphisms are suspected play a role in determining of its plasma levels. The aim of this study is to analyze the association between VEGF936C>T polymorphism and degree of atrophy in gastritis patient. Atrophy is preliminary lesion before the occurrence of gastric cancer. Methods: This crossectional study included gastritis patient in Permata Bunda Hospital. Endoscopy was performed to assess the gastric mucosae and the tissue biopsy was taken. VEGF936C>T was examined by Polymerase Chain Reaction (PCR). Results: Among sixty gastritis patients that included in this study, 23.4% shows atrophy. There is a significant relationship between VEGF 936C>T polymorphism and the degree of atrophy. A significant association is also found between CC genotype and allele C and degree of atrophy (p<0.05). Conclusion: There is a significant relationship between VEGF 936C>T polymorphism with the degree of atrophy.